To move or not to move: mobility decision-making in the context of welfare conditionality and paid employment. Issue 5 (3rd September 2019) - Marston, Greg; Zhang, Juan; Peterie, Michelle; Ramia, Gaby; Patulny, Roger; Cooke, Emma
ABSTRACT: The mobility and agency of the unemployed have rarely been examined together in welfare administration. Mobility research has much to offer the (im)mobility of low-skilled and unemployed workers. The article begins by critically examining dominant public discourse and policy reforms that stigmatise the assumed immobility of the unemployed. Drawing on empirical data from in-depth interviews with people on income support payments in Australia, it then offers a critical view on the mobility decision-making processes of these job-seekers. Building on previous research concerning the politics of mobility, it shows that structural inequalities impact mobility choices, making relocation difficult for many job-seekers. At the same time, it highlights the localised mobility that job search now involves, complicating orthodox associations between mobility and power – as well as assumptions that job-seekers are immobile.